OFR-30(2)-80 Microseismic Monitoring Of A Longwall Coal Mine - Volume II - Determination Of Seismic Velocity - H. Reginald Hardy (The National Institute for Occupational Safety and Health (NIOSH), 1977)
This report is Volume II of a three volume final report dealing with the microseismic monitoring of a longwall coal mine. The research presented in Volume II is concerned with the evaluation of field techniques for obtaining seismic velocity data required for computing microseismic source locations. The report describes the evaluation of a number of different field techniques and the seismic velocity data obtained at the Greenwich mine site where the micro-seismic studies, described in Volume I of the final report, were carried out. Three different methods were employed to evaluate seismic velocities, namely; surface refraction, down-hole, and transmission. In all cases the seismic sources were either located on surface (mechanical impact) or near-surface (explosive charges). It was found that a mechanical energy source could be conveniently utilized to determine shallow velocities and make bedrock-regolith interface depth determinations. For deeper velocity determinations suitable explosive charge sources Here required. In general, refraction data did not always plot in a linear manner and some subjective interpretation was necessary. The down-hole method was found to be useful for incremental vertical velocity evaluation, however, the transmission method provided the most consistent average vertical velocity data. At the Greenwich site seismic velocities were found to be anisotropic with values ranging from 9,551 to 10,739 feet per second depending on direction.